Soluble Guanylate Cyclase Stimulator, BAY41-8543: A Promising Approach for the Treatment of Chronic Heart Failure Caused by Pressure and Volume Overload - Martišková, Adriana; Sýkora, Matúš; Andelová, Natália; Ferko, Miroslav; Gawrys, Olga; Andelová, Katarína; Kala, Petr; Červenka, Luděk; Szeiffová Bačová, Barbara (Pharmacology research & perspectives, 2025)
Heart failure (HF) is a leading cause of morbidity and mortality, often driven by prolonged exposure to pathological stimuli such as pressure and volume overload. These factors contribute to excessive oxidative stress, adverse cardiac remodeling, and dysregulation of the nitric oxide-soluble guanylate cyclase-cyclic guanosine monophosphate (NO-sGC-cGMP) signaling pathway. Given the urgent need for effective treatments, this study investigated the potential of sGC stimulators to mitigate HF progression. We utilized male hypertensive Ren-2 transgenic (TGR) rats and a volume-overload HF model induced by an aortocaval fistula (ACF). Rats received the sGC stimulator BAY 41-8543 (3 mg/kg/day) for 30 weeks, while normotensive Hannover Sprague-Dawley rats served as controls. At the study endpoint (40 weeks of age), left ventricular tissue was analyzed using mass spectrometry, Western blotting, and histological assessment. TGR rats treated with sGC stimulators exhibited a significant increase in key antioxidant proteins (SOD1, CH10, ACSF2, NDUS1, DHE3, GSTM2, and PCCA), suggesting enhanced resistance to oxidative stress. However, sGC stimulator treatment also upregulated extracellular matrix remodeling markers (MMP-2, TGF-β, and SMAD2/3), which are typically associated with fibrosis. Despite this, Masson's trichrome staining revealed reduced collagen deposition in both TGR and TGR-ACF rats receiving sGC stimulators. Notably, all untreated TGR-ACF rats succumbed before the study endpoint, preventing direct assessment of sGC stimulator effects in advanced HF. These findings highlight the therapeutic potential of sGC stimulators in HF, particularly through their antioxidant effects. However, their concurrent influence on fibrosis warrants further investigation to optimize treatment strategies.
Keywords: pyrazoly; Oxidative Stress; Morpholines; morfoliny; oxidační stres; Heart Failure; rozpustná guanylátcyklasa; srdeční selhání; pyrimidiny; Ventricular Remodeling; potkani transgenní; Guanylyl Cyclase C Agonists; agonisté guanylátcyklasy; renin‐angiotensin system; heart failure with reduced ejection fraction; krysa rodu Rattus; soluble guanylate cyclase stimulator; reactive oxygen/nitrogen species; zvířata; Rats, Transgenic; Soluble Guanylyl Cyclase; potkani Sprague-Dawley; Male; Rats; Rats, Sprague-Dawley; Animals; Pyrimidines; mužské pohlaví; Pyrazoles; Disease Models, Animal; remodelace komor; modely nemocí na zvířatech